Pelatihan Mengelas dengan Kelengkapan Keselamatan dan Kesehatan Kerja (K3) - Sariman, Farid; Cipto (Yayasan Kawanad, 2023)
Welding technology is an applied technology that can be applied to society as a service company (welding contractor). The welding services business is a productive economic sector and has a wide range of markets, for example, the domestic market i.e. the manufacture of walkways, fences, canopies and d'Agliannes, as well as the transport sector for the repair and modification of automobiles. The use of welding technology in the community is based on training models. Through the PKM UNMUS 2022 programme, the PKM team is providing welding training using industrial safety equipment (K3) to the daily fish packing workers in Karang Inda Village, Merauke. Welding training is the solution for unskilled workers to increase their productivity. Training activities include socializing the community service program, training in welding theory through personal presentations and lectures, welding hands-on, and providing an understanding of K3 procedures and the use of PPE in the welding field. We hope that through this series of social contribution activities based on the social collaboration service SKIM, participants in the social contribution collaboration program will be able to acquire welding technology knowledge and skills for entrepreneurship.